PENGARUH KOMUNIKASI KELUARGA BROKEN HOME PADA TINGKAT DEPRESI ANAK REMAJA DI KOTA MAKASSAR - Amnia Apriliana; Zelfia Zelfia; Sitti Rahmawati (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2020)
The purpose of the study was to find out the Effect of Broken Home Family Communication on the Level of Adolescent Depression in Makassar City. The research method used is Quantitative Research, using primary data and secondary data by providing questionnaires / statement sheets to 30 respondents who are willing to be respondents. The results showed that Broken Home Family Communication had a positive and significant effect on the Level of Adolescent Depression in Makassar City. Based on the results of partial test (t-test) hypothesis X obtained that Family Communication has a significant and positive influence on depression levels in broken home families. Testing the effect of communication variables on depression levels can be known by looking at the t calculated value for family communication of 6,697 and t table of 2.048, with significance of 0.000. The t value is greater than the t table and the significance value below 0.05 indicates the effect of the Communication variable on the Level of Child Depression